Re-Revision ACLR: Operative Considerations - Hansel Ihn MD; Elaine Shing MD; Travis Maak MD (Video Journal of Sports Medicine)
Background: Re-revision anterior cruciate ligament reconstruction (ACLR) is a challenging clinical problem. A multifactorial approach to this situation is necessary to address each patient’s needs fully. Indications: Persistent instability. Technique Description: Contralateral bone–patellar tendon–bone ACLR with tibial bone defect bone grafting and postfixation of the tibial bone plug. Concomitant lateral extra-articular tenodesis was also performed. Results: At the 12-week follow-up, the patient had regained full range of motion and demonstrated sagittal stability on examination. However, with published data consistently demonstrating low return to preinjury level of activity, we remain cautiously optimistic with regard to her eventual outcome. Discussion/Conclusion: While it is important to be privy to the latest literature, it is also important to consider each patient’s case individually. Consideration should be given to the patient’s pertinent history and physical examination findings and not just radiographic parameters. Revision situations often present unforeseen challenges, so it is important to have contingency plans in place. Adopting techniques that minimize potential challenges, such as tunnel convergence, can be critical in successfully completing a surgery. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.